2005
DOI: 10.1002/hlca.200590136
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Strecker Reaction under High Pressure

Abstract: For the first time, uncatalyzed, high‐pressure (0.6 GPa) reactions with ketones have proven to be a powerful way to perform the three‐component Strecker synthesis of α‐amino nitriles in high yields. Two types of double Strecker reactions were achieved, but attempts to perform triple Strecker reactions were unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 64 publications
0
19
0
1
Order By: Relevance
“…It has been reported that the Strecker reaction of acetophenone even with the activated amine 3,4,5-trimethylaniline using metal triflates and acetonitrile as the solvent gave very poor yield of the product (47)(48)(49). We found that a similar reaction of acetophenone with aniline and TMSCN (cyanide source) in dichloromethane using Ga(OTf) 3 as a catalyst proceeds smoothly under mild conditions (room temperature, 5 h) giving the corresponding ␣-aminonitrile in excellent yield and high purity ( Table 2, entry 1), despite that the direct Strecker reaction using aromatic ketones and aromatic amines has been repeatedly cited in the literature as a challenge (6,7,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We performed the reaction with a variety of ketones and anilines at room temperature in dichloromethane, and in all cases high yields of the nitrile products were obtained emphasizing the generality of our methodology.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been reported that the Strecker reaction of acetophenone even with the activated amine 3,4,5-trimethylaniline using metal triflates and acetonitrile as the solvent gave very poor yield of the product (47)(48)(49). We found that a similar reaction of acetophenone with aniline and TMSCN (cyanide source) in dichloromethane using Ga(OTf) 3 as a catalyst proceeds smoothly under mild conditions (room temperature, 5 h) giving the corresponding ␣-aminonitrile in excellent yield and high purity ( Table 2, entry 1), despite that the direct Strecker reaction using aromatic ketones and aromatic amines has been repeatedly cited in the literature as a challenge (6,7,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We performed the reaction with a variety of ketones and anilines at room temperature in dichloromethane, and in all cases high yields of the nitrile products were obtained emphasizing the generality of our methodology.…”
Section: Resultsmentioning
confidence: 92%
“…Efficient, clean, and direct three-component Strecker reaction using ketones is difficult. Quite often, these reactions have to be carried out stepwise (preparation of imines first followed by cyanide addition) (2,3) or under high pressure conditions (6,7). Use of ammonia or ammonium salts in the presence of cyanides has been described (8)(9)(10)(11)(12)(13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amines were selected to illustrate a range of reactivities i.e. from aromatic to aliphatic and cyclic derivatives and as Table 1 illustrates, in the case of aniline (12), benzylamine (13) and phenylpropylamine (14), excellent yields were again obtained using analogous conditions to those employed for 2-phenylethylamine (7). However, in the case of pyrrolidine (15), which upon reaction with 4-bromobenzaldehyde (6) affords an iminium ion as the reactive intermediate, quantitative conversion of the aldehyde 6 to (4-bromophenyl)pyrrolidin-2-ylacetonitrile (16) was obtained at the higher flow rate of 20 µL min -1 , affording an increase in the reaction throughput compared to the primary amines investigated.…”
Section: Generality Of the Techniquementioning
confidence: 99%
“…These range from the use of organic solvents and alternative cyanide sources, [5] to the use of Lewis acid catalysts, [6][7][8][9] guanidine HCl, [10] ionic liquids, [11,12] catalyst-free [13] examples and even those conducted at elevated pressures (0.6 GPa). [14] Despite these advancements, the reaction still suffers from numerous drawbacks including the use of elevated reaction temperatures, extended reaction times, expensive homogeneous catalysts, an excess of the cyanide source and variable yields, which preclude the use of the Strecker reaction on a production scale.…”
Section: Introductionmentioning
confidence: 99%